1985
DOI: 10.1111/j.1365-2621.1985.tb01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and storage stability of commercial anhydrous milk fat and hydrogenated oils

Abstract: Two brands of ghee, three brands of butter oil and two brands of hydrogenated oils were examined for compositional properties and keeping quality. Analysis indicated that the samples were within the usual requirements, except one ghee sample which had a very high initial rate of free fatty acids (FFA).During storage the FFA and peroxide values (PV) increased. The increase in FFA was more obvious at 20°C than at 35"C, but in general the increase was not large. The PV showed a faster increase at 35°C than at 20°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Both Covi 70 and T 25 had a significant effect in reducing hydrolysis as compared to the control and Covi 50, but were not significantly different from each other emphasizing the role of the natural antioxidant Covi 70 in this respect. These results are in accordance to Thakar et al (1984), Iskandar et al (1985) and Warner (2003) who reported the effect of some natural plant antioxidants in controlling hydrolytic rancidity in cow's ABF during storage.…”
Section: Resultssupporting
confidence: 92%
“…Both Covi 70 and T 25 had a significant effect in reducing hydrolysis as compared to the control and Covi 50, but were not significantly different from each other emphasizing the role of the natural antioxidant Covi 70 in this respect. These results are in accordance to Thakar et al (1984), Iskandar et al (1985) and Warner (2003) who reported the effect of some natural plant antioxidants in controlling hydrolytic rancidity in cow's ABF during storage.…”
Section: Resultssupporting
confidence: 92%